1981
DOI: 10.1111/j.1365-2672.1981.tb00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Aspects of Cold Cleaning with an lodophor of Milk Pipeline Installations

Abstract: Over a period of three years bacteriological comparisons were made of a method of cleaning pipeline milking machines with (I) cold iodophor solution (cold method), (2) a chlorinated alkaline solution at 5540°C circulated for 10 min (hot method), and (3) acidified boiling water (ABW method). Rinse samples from the entire installations gave the best results with the ABW method. The cold method favoured a psychrotrophic flora, coliform bacteria or lactic streptococci, depending on the part of the milking machine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In general, there was a decline in the number of bacteria recovered by the water during rinsing. The rate of this decline appeared to be dependent on the level of Contamination, as previously shown with clusters (Richard & Auclair 1962), and also the types of bacteria (Cousins 1963). As bacteria are derived mainly from intricate parts of the milking machines (Cousins 1963;McCulloch 1963;) this rate of decline may also depend on the design of the milking machines.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…In general, there was a decline in the number of bacteria recovered by the water during rinsing. The rate of this decline appeared to be dependent on the level of Contamination, as previously shown with clusters (Richard & Auclair 1962), and also the types of bacteria (Cousins 1963). As bacteria are derived mainly from intricate parts of the milking machines (Cousins 1963;McCulloch 1963;) this rate of decline may also depend on the design of the milking machines.…”
Section: Discussionmentioning
confidence: 53%
“…The teat-cup assembly was connected to the vacuum line and after pulsating for 5 min, the liquid was recovered. Three rinse liquids were compared: sterile water, sterile skimmed milk (Richard & Auclair 1962) and whole milk pasteurized at 63.5"C for 30 min.…”
Section: Cluster Rinsesmentioning
confidence: 99%
See 2 more Smart Citations
“…From a practical point of view, there is a need for an interpretation of the results of sampling surfaces in terms of milk contamination. It was previously demonstrated that, provided sampling is done according to particular precautions, the number of bacteria found on the surface of milking machines cleaned with present methods is negligible (Richard 1981). This is not the case for the contamination of milk by teat skin (Piton & Richard 1982).…”
Section: Discussionmentioning
confidence: 79%